Atherosclerosis-Driven Treg Plasticity Results in Formation of a Dysfunctional Subset of Plastic IFNγ+ Th1/Tregs. Issue 11 (11th November 2016) - Butcher, Matthew J.; Filipowicz, Adam R.; Waseem, Tayab C.; McGary, Christopher M.; Crow, Kevin J.; Magilnick, Nathaniel; Boldin, Mark; Lundberg, Patric S.; Galkina, Elena V.
Abstract : Rationale: : Forkhead box P3 + T regulatory cells (Tregs) are key players in maintaining immune homeostasis. Evidence suggests that Tregs respond to environmental cues to permit or suppress inflammation. In atherosclerosis, Th1-driven inflammation affects Treg homeostasis, but the mechanisms governing this phenomenon are unclear. Objective: : Here, we address whether atherosclerosis impacts Treg plasticity and functionality in Apoe − /− mice, and what effect Treg plasticity might have on the pathology of atherosclerosis. Methods and Results: : We demonstrate that atherosclerosis promotes Treg plasticity, resulting in the reduction of CXCR3 + Tregs and the accumulation of an intermediate Th1-like interferon (IFN)-γ + CCR5 + Treg subset (Th1/Tregs) within the aorta. Importantly, Th1/Tregs arise in atherosclerosis from bona fide Tregs, rather than from T-effector cells. We show that Th1/Tregs recovered from atherosclerotic mice are dysfunctional in suppression assays. Using an adoptive transfer system and plasticity-prone Mir146a −/− Tregs, we demonstrate that elevated IFNγ + Mir146a −/− Th1/Tregs are unable to adequately reduce atherosclerosis, arterial Th1, or macrophage content within Apoe −/− mice, in comparison to Mir146a +/+ Tregs. Finally, via single-cell RNA-sequencing and real-time -polymerase chain reaction, we show that Th1/Tregs possess a unique transcriptional phenotype characterized by coexpression of Treg and Th1 lineage genes and a downregulation of Treg-related genes, including Ikzf2, Ikzf4, Tigit, Lilrb4, and Il10 . In addition, an ingenuity pathway analysis further implicates IFNγ, IFNα, interleukin-2, interleukin-7, CTLA-4 (cytotoxic T-lymphocyte–associated protein 4), T-cell receptor, and Csnk2b-related pathways in regulating Treg plasticity. Conclusions: : Atherosclerosis drives Treg plasticity, resulting in the accumulation of dysfunctional IFNγ + Th1/Tregs that may permit further arterial inflammation and atherogenesis. Abstract : Supplemental Digital Content is available in the text.